GAYA PARENTING ORANG TUA DALAM PEMBENTUKAN KARAKTER DAN KEPRIBADIAN ANAK - Farah Kamelia Ali Putri; Muyasaroh; Endah Mujiati (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2022)
Parents have a major contribution in shaping the personality of a child. One of them is through the parenting style given by parents to their children. There are three types of parenting that parents can apply to their children, namely: democratic parenting, permissive parenting and authoritarian parenting. Democratic parenting is a parenting style in which parents encourage children to talk about what they want. Authoritarian parenting is parenting where parents are the makers of all decisions, children must be submissive, obedient and may not ask questions. Meanwhile, permissive parenting has the characteristics of parents giving full freedom for what their children want to do. The choice of parenting style must be considered as to how it impacts the child's development. Not only physical development but the development of the child's personality. There are several differences in parenting styles given by parents to their children. This is influenced by several factors including socioeconomic level, education level, personality, and the number of children they have.